The Slusshy / Jeslyn Puti Othman - Jeslyn Puti, Othman (2020)
The Slusshy is a business under food and beverage (F&B) industry. We are home-based dessert seller which provide an up-to-date dessert that freshly made upon order. We can deliver the dessert to customers’ addresses or customers can also pick-up the dessert at my house. The concept of this business is more to elegant but minimalist. We serve fresh desserts with beautiful decorations and pack with minimalist boxes. The look is minimalist but it can be seen as expensive eventhough we sell at normal price. We offered our five (5) main desserts as they always demand on these dessert. We serve two sizes of pavlova which are pavlova cake and mini pavlova. Our customers can choose any two of three fruits offered as the toppings of their pavlova. We always have stocks of blueberry, strawberry and kiwi. We only use a these kind of fruits to ensure that the pavlova can still merged with that fruits’ tastes. We are avoiding watery fruits as to protect our dessert quality, taste and look. We also provide burnt cheesecake as it went viral these days along with the batik cheesecake. We limit the burnt cheesecake for only ten (10) of it a day. However, we made the batik cheesecake everyday and chill them in the chiller. We sell the batik cheesecake by size and by slice. Our last main dessert that always been purchased for events is macaroon. We noticed that macaroon gives an elegant look to the event, thus we decided to give the flavour that is lso bring the premium taste to the macaroon. We have peanut, nutella and mocha as the fillings. Our target market is the people around and the youngster. This is because teenagers nowadays always look for something nice to shot and post on their social media. As I am the first entrepreneur in this small town who bravely taking risk to run this business, I believe that I am able to go much far than this as long as I maintain and keep upgrading my products and customer service. Surely, before I manage to run this business, I made the calculations and proudly I can survive with this business because it is profitable.